Approaches to Serving Rural Older Adults in State Plans on Aging: A Policy Content Evaluation. (October 2022) - Henning-Smith, Carrie; Powell, Mary Anne; Lahr, Megan
Every state is required to submit a State Plan on Aging describing how it will use resources from the Older Americans Act (OAA), including a section specific to serving rural older adults. This paper describes a policy content evaluation of all 50 State Plans on Aging, focusing on Section 307(a)(10), which describes how states will serve rural older adults. We identified the most common and innovative approaches to using OAA funds to serve rural older adults across states. The most common information included about using OAA funds to serve rural older adults was describing the funding formula used to allocate resources. However, states varied in their definition of rural and in the details of their funding formulas. A minority of states also described additional approaches to serving rural older adults, including prioritizing Black, Indigenous, or rural residents of color; outreach; and targeted service delivery.